Supermasi Mahkamah Konstitusi Dalam Melakukan Judicial Review Terhadap Undang-Undang - Pramesti, Novalia Cahyaning Setyo (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This article discusses and proposes an integrated review of laws and regulations by the Constitutional Court. Discusses the problem regarding the authority of the Constitutional Court in conducting a review of the ratification law against the 1945 Constitution. Judicial review in the common law legal system is often understood as efforts to review laws and regulations carried out by the agency judiciary, although in the context of a wider scope of authority, because sometimes they also test administrative products (administrative Acts). Norms testing carried out by the Constitutional Court theoretically starts from abstract norms as an implication of the position of the Constitutional Court which is a norm court and examines it against constitution. To assess the constitutionality of law norms, then norms abstract which will be the focus of the MK's examination. This can lead to problems regarding the clarity of the authority to review ratification laws by the Constitutional Court in the future. This study uses the literary method with the conclusion that the Constitutional Court has the authority to review ratification laws that are contrary to the 1945 Constitution, but does not have the authority to examine the attachments to ratification laws that contain international agreement material. Testing ratification laws is limited to determining the constitutionality of the ratification of an international treaty through ratification laws.